Site-Specific Antibody Conjugation to Engineered Double Cysteine Residues - Qun Zhou; Josephine Kyazike; Ekaterina Boudanova; Michael Drzyzga; Denise Honey; Robert Cost; Lihui Hou; Francis Duffieux; Marie-Priscille Brun; Anna Park; Huawei Qiu (MDPI AG, 2021)
Site-specific antibody conjugations generate homogeneous antibody-drug conjugates with high therapeutic index. However, there are limited examples for producing the site-specific conjugates with a drug-to-antibody ratio (DAR) greater than two, especially using engineered cysteines. Based on available Fc structures, we designed and introduced free cysteine residues into various antibody CH2 and CH3 regions to explore and expand this technology. The mutants were generated using site-directed mutagenesis with good yield and properties. Conjugation efficiency and selectivity were screened using PEGylation. The top single cysteine mutants were then selected and combined as double cysteine mutants for expression and further investigation. Thirty-six out of thirty-eight double cysteine mutants display comparable expression with low aggregation similar to the wild-type antibody. PEGylation screening identified seventeen double cysteine mutants with good conjugatability and high selectivity. PEGylation was demonstrated to be a valuable and efficient approach for quickly screening mutants for high selectivity as well as conjugation efficiency. Our work demonstrated the feasibility of generating antibody conjugates with a DAR greater than 3.4 and high site-selectivity using THIOMABTM method. The top single or double cysteine mutants identified can potentially be applied to site-specific antibody conjugation of cytotoxin or other therapeutic agents as a next generation conjugation strategy.